PENGARUH PENDEKATAN PROBLEM POSING TERHADAP PRESTASI BELAJAR & KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS V SEKOLAH DASAR - Nurharyanto, Dwi Widyastuti; Jailani, Jailani (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
This research is a quasi-experimental research that uses one experimental class and one control class. The experimental class used problem posing, which was SDN Madusari I, and one control class was not given treatment, which was SDN Potrojayan. This research focuses on students' learning achievement and mathematical reasoning abilities which are measured using test instruments in the form of short answer questions and essay questions. This research aims to describe: 1. the influence of the Problem-posing approach on the learning achievement of class V students, 2. the effect of Problem-posing on the mathematical reasoning abilities of class V students. The hypothesis test used is a univariate test. The research results show that, 1. Asking problems has no effect on learning achievement with a significance value of 0.067 (p > 0.05), 2. Asking problems has no effect on mathematical reasoning abilities with a significance value of 0.393 (p > 0.05). Based on the results of the analysis, problem formation creates obstacles for students, namely the difficulty of understanding the meaning of the problem and confirming it. The application of problem poses to influence learning achievement and mathematical reasoning abilities was not successful so other alternatives can be considered for further research.